Configuration and the Role of Community Leaders in the Conflict of Natural Resources of Limestone Mining for the Cement Industry in Rembang Indonesia - Rokhmad, Abu (International Journal of Energy Economics and Policy, 2020)
This research examines the conflicts of natural resources in Kendeng Rembang, Central Java and how the position of ulama in the conflict. This study is a field research with a qualitative approach. Data was collected by interview, observation, and document study methods. Documents stored on the internet are widely quoted sources. The analysis uses qualitative descriptive. The results of the research show that the conflict occurred because residents refused limestone mining carried out by PT. Semen Indonesia (PT. SI) in the Kendeng Mountains which are rich in natural resources. Residents are concerned that mining limestone - as a raw material for making cement - can damage the environment. This conflict is a vertical and structural conflict. The main actor is a citizen dealing with PT. SI and the government. Restu and ulama support are contested by both parties. As a result, the ulama’s view of the conflict was divided into two parts. Keywords: Conflict, Natural Resources, Kendeng Mountains, Mines, Limestone, Ulama. JEL Classification: Q34 DOI: https://doi.org/10.32479/ijeep.8321